2014
DOI: 10.15252/msb.20145141
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular network structure and regulatory motifs in the human hematopoietic system

Abstract: The hematopoietic system is a distributed tissue that consists of functionally distinct cell types continuously produced through hematopoietic stem cell (HSC) differentiation. Combining genomic and phenotypic data with high-content experiments, we have built a directional cell–cell communication network between 12 cell types isolated from human umbilical cord blood. Network structure analysis revealed that ligand production is cell type dependent, whereas ligand binding is promiscuous. Consequently, additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
69
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 68 publications
10
69
0
Order By: Relevance
“…63 Using combined genomic and phenotype data, this work has recently been expanded to generate a directional cell-cell communication network between 12 human hematopoietic cell types isolated from umbilical cord blood. 64 Microfluidics technology already offers opportunities to monitor single cells responding to an external signal, as well as to quantify signaling molecules secreted by individual HSPCs. 65 A blueprint for the integration of inter-cellular communication into regulatory network models has been provided by Eric Davidson's pioneering work on sea urchin development, 1 which is likely to provide an important starting point for the future generation of similarly comprehensive network models for blood cell development.…”
Section: Discussionmentioning
confidence: 99%
“…63 Using combined genomic and phenotype data, this work has recently been expanded to generate a directional cell-cell communication network between 12 human hematopoietic cell types isolated from umbilical cord blood. 64 Microfluidics technology already offers opportunities to monitor single cells responding to an external signal, as well as to quantify signaling molecules secreted by individual HSPCs. 65 A blueprint for the integration of inter-cellular communication into regulatory network models has been provided by Eric Davidson's pioneering work on sea urchin development, 1 which is likely to provide an important starting point for the future generation of similarly comprehensive network models for blood cell development.…”
Section: Discussionmentioning
confidence: 99%
“…For example, can we turn simulations and data into discovery and design? How can we interface synthetic and endogenous control (as recently started by Qiao et al, 2014)? Can the spatial and temporal scales observed in development be aligned with those in simulations?…”
Section: Designed Control: Insights From Physics and Engineeringmentioning
confidence: 99%
“…The network construction is described in detail by Qiao et al [26]. Briefly, potential ligand-receptor interactions were determined based on a list (S1 Table) that was compiled by interrogating public protein interaction databases and literature mining.…”
Section: Network Construction and Visualizationmentioning
confidence: 99%
“…Gene expression-based cell-cell communication networks, which were used in this study, have been demonstrated as valuable tool to dissect principles of paracrine interaction within the complex hematopoietic system and identify key signals that regulate the fate of hematopoietic stem cells [26][27][28]. For the first time, we extended this tool to non-hematopoietic cells and systematically examined the potential cell-cell communication between BCC, MSC and HSPC insilico with special respect to metastatic progression and modulation of bone marrow function.…”
Section: Introductionmentioning
confidence: 99%